Lactobacillus fermentum LAB 9-fermented soymilk with enriched isoflavones and antioxidants improved memory In vivo - E.F. Mohamad Fakri; Lim, S.M.; N. H. Musa; M. Hazizul Hasan; A. Adam; K. Ramasamy (Penerbit Universiti Kebangsaan Malaysia, 2016)
This study examined lactic acid bacteria (LAB)-fermented soymilk for their ability in hydrolyzing glucosides to aglycones and corresponding antioxidant capacity and memory enhancing effect. Twelve LAB isolated from Malaysian fermented food and milk products were incubated in commercially available soymilk for 48 h. Generally, soymilk supported LAB growth and significantly increased (p<0.05) conversion to bioactive aglycone by 2.1-6.5 fold when compared to unfermented soymilk. Lactobacillus fermentum LAB 9- fermented soymilk, in particular, was presented with increased total phenolic content (+10%) as opposed to unfermented soymilk. Lactobacilli (LAB 10-12)- and pediococci (LAB 5)-fermented soymilk elicited maximal DPPH radical-scavenging activity. LAB 1, 7, 8, 9 and 12 exhibited significantly higher (p<0.05) ferrous ion chelating activity when compared to control. Interestingly, LAB 9 had significantly improved memory deficit (p<0.05) in LPS-challenged mice. LAB-enriched nutritional value of soymilk could be useful against oxidative stress and memory deficit.